Assessing Ecological Tourism in Pulau Banyak: An Analysis Through Fiqh Al-Bi'ah Principles - Jamhuri, Jamhuri; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to provide an Islamic legal analysis of the concept of ecological tourism in Pulau Banyak District through the perspective of Fiqh al-Bi'ah. Fiqh al-Bi'ah, as part of Islamic teachings, offers ethical and religious guidance in preserving the environment. However, the phenomenon of tourism development often clashes with environmental welfare agendas. Halal tourism in Pulau Banyak still faces problems despite being regulated by Aceh Qanun Number 8 of 2013. Therefore, an objective regulation and a redefinition of the halal tourism concept in Pulau Banyak, framed within Maqasid Sharia and aligned with the Fiqh al-Bi'ah concept, are urgently needed. There are still structural inequalities in Pulau Banyak District. The halal tourism development policy in Pulau Banyak should address the various inequalities that have occurred so far. The common inequalities found in Pulau Banyak District include regulatory disparities between tourism and conservation policies, social inequalities between religious values, customary rules, and the perception that tourist areas are free zones, as well as economic access inequalities from tourism activities in Pulau Banyak. The research method used is qualitative with a descriptive-analytical approach. Data were collected through observation and documentation of valid sources to capture the phenomena in Pulau Banyak District. The authors hope that this research can serve as a source of Islamic law in environmental regulation and as an effort to provide a contemporary fiqh paradigm in guiding the development of halal tourist areas that align with infrastructure development and increase environmental awareness among the community and tourists.